Keterlibatan dan Kontribusi Generasi Muda Terhadap Pembangunan Pertanian di Indonesia: Engagement and Contribution of the Young Generation to Agricultural Development in Indonesia - Khoirunnisa, Farina; Rozaki, Zuhud; Wulandari, Retno; Suryani, Cahyaningrum Arie (Universitas Muhammadiyah Yogyakarta, 2024)
The agricultural sector plays a crucial role in Indonesia's economy but is currently facing an ageing problem with low participation from the younger generation. This decline is influenced by several factors, including a pervasive negative view of agriculture, limited access to capital and technology, and a lack of encouragement or incentives for young farmers. This research aims to find out what factors make the younger generation reluctant to enter agriculture, how interested young people are in entering the world of agriculture, and what efforts or solutions can be made so that young people are interested in agriculture. This research applies an analytical descriptive method that focuses on current issues that are relevant. Information was obtained from reliable sources, then compiled, analysed and interpreted. Data sources include literature from related journals, theses, and other valid references. The results show that the younger generation has great potential to contribute significantly to the development of agriculture in Indonesia. They have favourable characteristics, such as creativity, innovation, and strong knowledge in technology. However, this potential has not been fully utilised. Therefore, efforts are needed to stimulate the involvement and contribution of the younger generation in advancing the agricultural sector in Indonesia. Such measures include but are not limited to 1) Increasing public awareness of the importance of agriculture. 2)Improving the access of the younger generation to capital and technology. 3)Providing incentives or encouragement for young farmers. 4)Creating an enabling environment for the development of the agricultural sector. It is hoped that these efforts will mobilise greater participation and contribution from the younger generation towards the development of the agricultural sector in Indonesia. This has the potential to increase agricultural productivity, achieve food self-sufficiency, and improve the overall welfare of society.